Penerapan Pendekatan Ontologi dalam Penelitian Kebijakan Pendidikan Vokasi di Era Digital - Prasetiyanto, Ari Eka; Nursalim, Mochamad; Kristanto, Andi (Universitas Muhammadiyah Makassar, 2024)
Vocational education in the digital era faces significant challenges in adapting to technological advancements and the demands of Industry 4.0. The ontological approach, which examines the nature and structure of reality, provides a conceptual framework for analyzing and formulating adaptive and relevant vocational education policies. This paper explores the application of the ontological approach in vocational education policy research, emphasizing the integration of information and communication technology into curricula, the enhancement of educators' competencies, and the development of learners' skills aligned with the requirements of the digital industry. Through an analysis of recent literature, it is evident that an ontological understanding of the elements within vocational education can support the design of policies that are more responsive to technological changes and labor market needs. This approach has significant implications, encouraging collaboration between educational institutions and industries, and promoting flexible, competency-based curriculum adjustments to meet the evolving demands of the digital age.